Y = -2x + 5 y =3x - 2
Since both equations are equal to 'y' you can set them equal to each other to solve.
-2x + 5 = 3x - 2 Subtract 3x from both sides
-5x + 5 = -2 Subtract 5 from both sides
-5x = -7 Divide -5 on both sides
x = 7/5
Plug 7/5 back in for x and solve for y.
y = -2(7/5) + 5
y = (-14/5) + (25/5)
y = 11/5
(7/5, 11/5) OR (1.4, 2.2)
Answer:
44
Step-by-step explanation:
Answer:
length= 9
width= 3
Step-by-step explanation:
x= width
length = x+6
x+6+x+6+x+x=24
4x+12=24
take 12 from both sides
4x= 12
x=3
There would be a hole when x = -4.
If you factor both the top and the bottom, you will see that the factor (x + 4) is in both the numerator and denominator. Therefore, the would be a hole when x = -4 because that would also make the denominator 0.